Islamic Education Curriculum Innovation: Integration of Full Day School Education Model in the National Education System - Elynawati; Usman, Nurodin; Mawardi, Imam (Urecol Journal. Part A: Education and Training, 2023)
The dynamics of life make human beings required to move with speed, accuracy, alertness, intellectual, emotional, spiritual development and creativity. With so many challenges, conventional methods will no longer be able to meet the needs of education in the present and future so a new educational concept called full day school emerges, where learning carried out in schools is carried out for a day full of informal atmosphere, not rigid, pleasing students, also full of creativity and innovation from teachers. The characteristics of this full day school system prioritize morals and academic achievement with the aim of providing a strong foundation for students and developing interests and talents and increasing the intelligence of students in all aspects. The advantages of full day school compared to regular schools are that children get a complete education including cognitive, affective, and psychomotor, more learning than play, high productivity, and the potential of children channeled through extracurricular activities at school. Research related to full day school that has been carried out shows that full day school has a positive influence on improving the character, morals, akhlaq, and academic achievement of students. This research is descriptive, using a qualitative approach. The data collection technique carried out is to use field observations, interviews and literature reviews.